Public Transportation Slang - Munawwir Hadiwijaya; Trisnian Ifianti; Yahmun Yahmun (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
As a product of creativity, slang continuously raises in society used to mark social and cultural differences. This study aims to discover terms of slang used by the community of public transportation drivers in Kacuk Malang, the process of its formation, the meaning it refers to, and the purpose of its usage. Qualitative design is used as the research method by using the following steps in collecting and analyzing data. The observation was done to gain information about using slang in conversation among public transportation drivers and followed up by interviewing ten drivers. The study found that Slang was used for a variety of purposes. Initially, as their code language. As a language for jokes, second. Third, they use Bahasa Jawa (Javanese language) as words or supplementary language to keep the discourse fresh and further demonstrate their Kacuk community identity. Fifth, as a way to get to know one another better. The final one was for their regular discussions.